2022
DOI: 10.20945/2359-3997000000490
|View full text |Cite
|
Sign up to set email alerts
|

Healthy lifestyle gone bad: effect of the COVID-19 pandemic on the daily habits of children and adolescents with type 1 diabetes

Abstract: Objective: To assess caregivers' perception about the changes in the daily habits of children and adolescents with type 1 diabetes during the COVID-19 pandemic. Subjects and methods: Primary caregivers of youth aged ≤18 with or without type 1 diabetes were selected for the diabetes and the control groups. Caregivers estimated the youth's time (hours) of physical activity and screen time before and during the pandemic, and rated the quality of eating habits and medication adherence from 0 to 10. The primary out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…A study in Brazil found that during the pandemic, eating habits worsened among adults with type 1 diabetes. 72…”
Section: Resultsmentioning
confidence: 99%
“…A study in Brazil found that during the pandemic, eating habits worsened among adults with type 1 diabetes. 72…”
Section: Resultsmentioning
confidence: 99%
“…A study involving 764 participants highlighted that eating habits were significantly worse among youths with diabetes compared to those without diabetes. This underscores the importance of lifestyle education during the pandemic [ 37 ].…”
Section: Epidemiologymentioning
confidence: 99%